Piezoceramic composite actuators for a solid-state variable-camber wing. (May 2014) - Bilgen, Onur; Friswell, Michael I
A solid-state piezocomposite variable-camber morphing wing is proposed for fixed-wing aircraft that operate in the low Reynolds number regime. An experimental evaluation of the wing which employs a continuous inextensible surface, continuous boundary conditions, and surface-bonded piezoelectric actuators is presented. The partially active surface is designed to have sufficient bending stiffness in the chordwise and spanwise directions to sustain shape under aerodynamic loading. In contrast, the in-plane stiffness is relatively high; however, the necessary deformations that are required to change the aerodynamic response can still be attained while maintaining the surface area constant. Coupled with the continuous boundary conditions and the spar structure, the prototype piezocomposite wing can achieve desired change in aerodynamic response quantified in terms of lift coefficient and lift-to-drag ratio. The experimental variable-camber, shell-like, morphing wing sustains aerodynamic loading at the maximum tested free-stream velocity of 22.8 m/s and at a Reynolds number of 251, 000 without degradation of aerodynamic authority.